Performance Analysis of Different Tie-Line for Synchronization of 12-Area Two Interconnected Thermal Power Grid - Sahu, Pankaj Kumar (Asian Journal of Electrical Sciences, 2017)
This paper represents the advantages of HVAC-HVDC parallel tie-line as compare to the Flexible AC Transmission System (FACTS) tie-line and normal HVAC tie-line for synchronization of 12-area two interconnected thermal power grid with its all 12 areas when load changed in power grid-1 (area-6). After load change in power grid-1 (area-6), 12-area two interconnected thermal power grid with its all 12 areas are synchronized at the same time only in case of HVAC-HVDC parallel tie-line. This paper also shows the Flexible AC Transmission System (FACTS) tie-line is better as compare to the normal HVAC tie-line. Performance analysis of different tie-line for synchronization or load (machine) frequency control of 12-area two interconnected thermal power grid is done in terms of settling time of frequency deviation of all 12 areas and settling time of tie-line power deviation of two interconnected areas or two interconnected power grid by using conventional integral controller when load changed in power grid-1 (area-6).